KEWENANGAN PENGISIAN ANGGOTA BAWASLU DI PROVINSI ACEH - T.Muhammad Nurdhia Ikhsan, Husni Jalil, Adwani. (Jurnal Ilmu Hukum, 2016)
Abstract: Article 1/ No.5/ Act No. 15/ Year 2011 on the Implementation of General Election states that